From an Idea to a Commercialized Product: Hard Lessons about Technology Transfer Learned During a 16 Year Journey - P. Glascock, Anthony (Technology Transfer and Entrepreneurship (Discontinued), 2014)
The 16 year process of moving an idea for a behavioral monitoring system developed within a university setting to a commercialized product funded by venture capital is discussed and a series of lessons learned during the process is highlighted. The article emphasizes the complexity inherent in technology transfer by describing, in detail, the route followed during the 16 years of development and commercialization which passed through five distinct stages: 1) the product idea; 2) development within the university; 3) moving development outside the university; 3) partnering with a large corporation; 4) venture capital; and 5) selling to General Electric. Insight is gained on the challenges of working in each of these different entities because of the use of ethnographic research methods during which the events that occurred at each stage were recorded in detail. Additionally, since the product being developed was protected by a series of patents it had a value which allowed access to the inner workings of each of the stages that is usually denied to researchers. Even though the technology transfer was ultimately successful, the overall message is cautionary; it is harder to commercialize than it appears. Although each technology transfer is different, a series of lessons are presented and discussed: don’t quit your day job; be nimble, flexible and agile; explore every avenue; expect failure; don’t go into commercialization to get rich; it takes more money than you think to be successful; and believe in your idea.
Keywords: lessons